Acute gastric mucosal lesions caused by acute infection of non‐HelicobacterpyloriHelicobacter: a case report. Issue 4 (11th May 2021) - Tsukadaira, Toshihisa; Hayashi, Seiichi; Ota, Hiroyoshi; Kobayashi, Natsuko; Sekiguchi, Yasuhiro; Kodaira, Himiko; Matsumoto, Takehisa; Horiuchi, Kazuki; Negishi, Tatsuya; Kurahashi, Mari
Abstract: Background: Non‐ Helicobacter pylori Helicobacter (NHPH) is not widely recognized as a cause of acute gastric mucosal lesions (AGML), as only a few cases of AGML caused by NHPH have been reported. We present here one case and examine the species and eradication of NHPH together with the three previously reported cases. Case presentation: A 52‐year‐old woman presented with a two‐day history of severe epigastric pain, nausea, and vomiting. An esophagogastroduodenoscopy showed mucosal edema, multiple erosions, and ulcerations in the antrum. Biopsy specimens taken from the antrum revealed long spiral‐shaped organisms, suggesting NHPH. As both serum anti‐ Helicobacter pylori ( H .  pylori ) antibody and H .  pylori stool antigen test were negative, this case was diagnosed as AGML caused by NHPH. After the administration of esomeprazole 20 mg for 14 days and the interval of the following 12 days, AGML was deemed to have been cured endoscopically. In addition, microscopic examination and PCR analysis confirmed the success of NHPH eradication. Conclusions: NHPH should be considered a probable cause of AGML in cases that are not attributed to the other causes already recognized. Taking probability of spontaneous eradication into consideration, it is appropriate to start eradication therapy after confirming the chronicity of NHPH infection.